Sovetskiye lyudi znayut: tam gde partiya, tam uspekh, tam pobeda!
Portrait of L. I. Breshnev over red background, quotes and texts over white background on the bottom half Original title: Советские люди знают: там где партия, там успех, там победа! PO-0355